Morphine Exacerbates Postfracture Nociceptive Sensitization, Functional Impairment, and Microglial Activation in Mice. (February 2019) - Li, Wen-Wu; Irvine, Karen-Amanda; Sahbaie, Peyman; Guo, Tian-Zhi; Shi, Xiao-you; Tawfik, Vivianne L.; Kingery, Wade S.; Clark, J. David
Editor's Perspective: What We Already Know about This Topic: Opiates, including morphine, remain a key component in the management of postsurgical pain; however, perioperative use of opiates is associated with a slower resolution of pain and functional status It is possible that the delayed recovery attendant with the administration of morphine may be attributable to morphine-induced enhancement of neuroinflammation What This Article Tells Us That Is New: In a mouse tibia fracture and intramedullary pinning model, injury-induced allodynia and neuroinflammation, in particular microglial activation, were significantly increased by morphine Reduction of microglial activation by an antagonist of the Toll-like receptor 4 attenuated the adverse effects of morphine The data are consistent with the premise that morphine increases nociceptive sensitization, functional impairment, and prolongs recovery; suppression of neuroinflammation, and in particular microglial activation, can mitigate the adverse effects of morphine Background: Emerging evidence suggests that opioid use immediately after surgery and trauma may worsen outcomes. In these studies, the authors aimed to determine whether morphine administered for a clinically relevant time period (7 days) in a tibia fracture orthopedic surgery model had adverse effects on postoperative recovery. Methods: Mice were given morphine twice daily for 7 days after unilateral tibial fracture and intramedullary pin fixation to model orthopedic surgery and limb trauma. Mechanical allodynia, limb-specific weight bearing, gait changes, memory, and anxiety were measured after injury. In addition, spinal cord gene expression changes as well as glial activation were measured. Finally, the authors assessed the effects of a selective Toll-like receptor 4 antagonist, TAK-242, on nociceptive and functional changes after injury. Results: Tibial fracture caused several weeks of mechanical nociceptive sensitization ( F (1, 216) = 573.38, P < 0.001, fracture + vehicle vs . sham + vehicle, n = 10 per group), and this change was exacerbated by the perioperative administration of morphine ( F (1, 216) = 71.61, P < 0.001, fracture + morphine vs. fracture + vehicle, n = 10 per group). In additional testing, injured limb weight bearing, gait, and object location memory were worse in morphine-treated fracture mice than in untreated fracture mice. Postfracture expression levels of several genes previously associated with opioid-induced hyperalgesia, including brain-derived neurotrophic factor and prodynorphin, were unchanged, but neuroinflammation involving Toll-like receptor 4 receptor–expressing microglia was observed (6.8 ± 1.5 [mean ± SD] cells per high-power field for fracture + vehicle vs . 12 ± 2.8 fracture + morphine, P < 0.001, n = 8 per /group). Treatment with a Toll-like receptor 4 antagonist TAK242 improved nociceptive sensitization for about 2 weeks in morphine-treated fracture mice ( F (1, 198) = 73.36, P < 0.001, fracture + morphine + TAK242 vs. fracture + morphine, n = 10 per group). Conclusions: Morphine treatment beginning at the time of injury impairs nociceptive recovery and other outcomes. Measures preventing glial activation through Toll-like receptor 4 signaling may reduce the adverse consequences of postoperative opioid administration. Abstract : In a mouse tibia fracture and intramedullary pinning model, injury-induced allodynia and neuroinflammation, in particular microglial activation, were significantly increased by morphine. Reduction of microglial activation by an antagonist of the Toll-like receptor 4 attenuated the adverse effects of morphine. The data are consistent with the premise that morphine increases nociceptive sensitization, functional impairment, and prolongs recovery; suppression of neuroinflammation, and in particular microglial activation, can mitigate the adverse effects of morphine.